Comparison of postural control in athletes under different loads - Nazarenko, A.S.; Mavliev, F.A.; Yusupov, R.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to analyse and compare the muscle control of athletes under various functional loads. Methods and structure of the study. The study was conducted at the Research Institute of Physical Culture and Sport at Volga Region State University of Physical Culture. It involved 227 male athletes with at least nine years of experience and sports qualifications ranging from second adult category to master of sports of the Russian Federation. Postural control was assessed using a stabilisation platform with biological feedback in a state of relative rest, as well as after vestibular, speed-strength and cyclic stepwise increasing physical exertion. Results of the study and discussion. Athletes engaged in situational sports have the most effective postural control system, which is manifested in better stabilography indicators under various functional loads. This is due to the need to compensate for diverse and unpredictable external factors, unlike cyclic sports, where variations are more predictable. Targeted sports, in turn, require high precision of postural adjustments, but not in complex conditions. The study confirms that versatility and skill transfer are formed in sports that require solving non-standard motor tasks in an unstable environment.